Analysis of Educational Value in Novel 9 Summers 10 Autumns Iwan Setyawan's work for elementary school children - Isnaini Nurhayati (Mitra Palupi, 2022)
Background: Novel is a literary work in the form of prose that discusses a work of imagination about the problems of a person's life or various other characters. One of the novel literary works that is interesting to analyze and study its educational value is the novel9 Summers 10 Autumns Iwan Setyawan's work which tells an interesting and inspiring story that can be a meaningful life lesson, where the value of education is so important that it is applied in everyday life. Purpose: The purpose of this research is to be used as teaching material for teachers in increasing reading interest, literary appreciation, and analyzing literary works and knowing the value of education in them. Design and methods: The research method used is content analysis (Content Analysis) with a qualitative descriptive approach, by describing the data in the form of words. The data collection technique uses a documentation study of the study of novel texts9 summers 10 autumns by Iwan Setiawan. Results: Research results from the novel9 summers 10 autumns have educational values ​​such as the value of truth, the value of goodness, the value of beauty, and the value of changing attitudes or procedures that can be taken for elementary school children and become teaching materials for teachers.